Pengaruh Penggunaan Media Video Animasi terhadap Peningkatan Pengetahuan Pencegahan Pelecehan Seksual pada Anak Usia Dini di Tk Aisyiyah Kota Bukittinggi - Kartika Mariyona; Pagdya Haninda Nusantri Rusdi; Mega Ade Nugrahmi; Wira Meiriza (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
In recent times, sexual abuse of children in Indonesia has been increasing, not only among adolescents, but also among young children who have been targeted by sexual offenders. With the high number of incidents of sexual harassment, the government issued a law as a preventive measure to reduce the level of sexual violence against children, namely Law No. 35 of 2014 concerning Child Protection. The purpose of this study was to see "The Effect of Using Video Animation Media on Increasing Knowledge of Prevention of Sexual Harassment in Early Childhood at Aisyiyah Kindergarten, Bukittinggi City". The introduction of knowledge education about sexual abuse in early childhood must of course be delivered in very interesting media. This research is a quasi-experimental study with a pre-test and post-test design without control using a simple random sampling technique. The number of respondents was 25 students of Aisyiyah Kindergarten, Bukittinggi City. Data analysis in this study used the Wilcoxon test